Rapid and Economic Access to Some NSAIDS-Based Bioactive Heterocycles. (17th October 2012) - Chavan, A. V.; Somani, R. R.; Kalantri, P. P.; Makhija, D. T.
Abstract : The use of microwave energy for the synthesis is considered as one of the alternate strategies. The present work includes the synthesis of some newer 2, 5-disubstituted-1, 3, 4-oxadiazole analogues using both conventional and alternate rapid methods.The conventional method involves the synthesis of the target molecules by using cyclodehydrating agent like POCl3, while the other method consists of using some catalytic reagents like PbO2 . Also, the short reaction time provided by microwave synthesis makes it ideal for the reaction. Hence, this project describes an efficient and operationally simple method for the microwave-assisted synthesis of some bioactive heterocycles based on NSAIDs.